2022
DOI: 10.1021/acs.jpca.1c08628
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Forms of NO on Iridium-Doped Rhodium Clusters in the Gas Phase Revealed by Infrared Multiple Photon Dissociation Spectroscopy

Abstract: The adsorption of an NO molecule on a cationic iridium-doped rhodium cluster, Rh 5 Ir + , was investigated by infrared multiple photon dissociation spectroscopy (IRMPD) of Rh 5 IrNO + • Ar p complexes in the 300−2000 cm −1 spectral range, where the Ar atoms acted as a messenger signaling IR absorption. Complementary density functional theory (DFT) calculations predicted two near-isoenergetic structures as the putative global minimum: one with NO adsorbed in molecular form in the on-top configuration on the Ir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In Figure 12, the NO dissociation propensity over several six-atomic cluster compositions, is plotted as a function of the highest calculated binding energy of atomic O to the cluster, we see a correlation between the two quantities. 111,116 This finding indicates that to be able to predict the NO dissociation efficiency, one should evaluate the binding energy of atomic oxygen to the material under debate. This forms a crucial refinement of work by Sakaki and coworkers, who conclude that dissociation is preferred by metals with strong N-and O-affinities (Run and Rhn in particular).…”
Section: Clusters Other Than Pure Rhodiummentioning
confidence: 99%
“…In Figure 12, the NO dissociation propensity over several six-atomic cluster compositions, is plotted as a function of the highest calculated binding energy of atomic O to the cluster, we see a correlation between the two quantities. 111,116 This finding indicates that to be able to predict the NO dissociation efficiency, one should evaluate the binding energy of atomic oxygen to the material under debate. This forms a crucial refinement of work by Sakaki and coworkers, who conclude that dissociation is preferred by metals with strong N-and O-affinities (Run and Rhn in particular).…”
Section: Clusters Other Than Pure Rhodiummentioning
confidence: 99%
“…However, this efficient NO dissociation was shown to be due to strong bonds of atomic N and O to the cluster, risking the poisoning of a potential catalytic site . An increased, but still relatively weak interaction was found for Ir-doped Rh clusters …”
Section: Introductionmentioning
confidence: 99%
“…Mackenzie and coworkers used mass spectrometry to investigate the adsorption of NO molecules onto Rh cluster cations, observing NO reduction for several cluster sizes under low-pressure conditions. They also investigated the geometrical structures of Rh clusters with IR multiple photon dissociation (IRMPD) spectroscopy. , Ichihashi and coworkers studied NO adsorption onto alloyed Rh clusters, finding NO reduction for alloys with Al and V . Recently, we conducted a series of spectroscopic experiments investigating the adsorption of NO onto clusters of several elements at sufficiently higher pressures, allowing thermal equilibration of the adsorption product. In the spectroscopic study of NO adsorption on cationic Rh clusters, Rh n + ( n = 6–16), we found that for all n studied, NO predominantly adsorbs in the molecular form on on-top sites of Rh n + , and that only a small fraction adsorbs dissociatively . For dissociative adsorption, the O atom tends to bind to a bridge site, whereas the N atom is found on either a bridge or a hollow site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these studies have been motivated by the use of rhodium in automotive three-way catalytic converters 9 and the reactions of N 2 O, [10][11][12] NO, [13][14][15][16][17][18][19][20][21][22] CO 23,24 and CO 2 25 have been extensively investigated on both pure and doped [26][27][28] rhodium clusters. Given that spectroscopic methods such as infrared multiple photon dissociation spectroscopy (IRMPD) 29 use mass spectroscopy to identify the species of interest, they generally provide information only about the products of reactions and reactivity studies therefore often include computational investigation, 30,31 typically using density functional theory (DFT), but sometimes including higher level methods such as CCSD(T).…”
Section: Introductionmentioning
confidence: 99%